2006
DOI: 10.1021/ja0645483
|View full text |Cite
|
Sign up to set email alerts
|

Topological Control in Heterometallic Metal−Organic Frameworks by Anion Templating and Metalloligand Design

Abstract: Several new heterometallic metal-organic frameworks (MOFs) based on tris(dipyrrinato) metalloligands and Ag+ salts are reported. MOFs were prepared systematically to examine the effects of the core metal ion, counteranion, and ligand structure on the topology of the resultant network. The effect of the metal ion (Fe3+ vs Co3+) on MOF structure was generally found to be negligible, thereby permitting the facile synthesis of trimetallic Fe/Co/Ag networks. The choice of anion (e.g., silver salt) was found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
178
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(190 citation statements)
references
References 56 publications
6
178
0
6
Order By: Relevance
“…It is suggested that the overall structure of the network is strongly influenced by the geometry and the size of the anion, together with its ability to interact with the metal center. [31] The flexible dihedral angles between the pyridine and triazole rings also provide the curva- Anion-exchange properties and the transformation from discrete cage to 3D coordination network: We explored the anion-exchange reactions of these cage-like architectures. After gently stirring 1 (0.5 mmol) in a 2:1 H 2 O/CH 3 CN solution containing 5 mmol NaClO 4 for about 6 h the resultant mixture was evaporated at room temperature for two weeks.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the overall structure of the network is strongly influenced by the geometry and the size of the anion, together with its ability to interact with the metal center. [31] The flexible dihedral angles between the pyridine and triazole rings also provide the curva- Anion-exchange properties and the transformation from discrete cage to 3D coordination network: We explored the anion-exchange reactions of these cage-like architectures. After gently stirring 1 (0.5 mmol) in a 2:1 H 2 O/CH 3 CN solution containing 5 mmol NaClO 4 for about 6 h the resultant mixture was evaporated at room temperature for two weeks.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Both homoleptic and heteroleptic organic ligands have been used in the preparation of cage complexes. [3] Although metalloligands have been extensively employed in the preparation of functional metal-organic frameworks, [4] fewer examples of discrete polyhedral complexes that involve the use of metalloligands have been reported. [5] Compared with organic ligands, metalloligands may function as bridging ligands with some additional advantages: 1) the introduction of new functionality, such as chirality and spectroscopic character; 2) flexible geometric control, which could avoid complex modification of the organic ligand structure; 3) the ability to assemble many components into a discrete entity.…”
mentioning
confidence: 99%
“…The development of advanced MOFs employs prefunctionalized moieties such as metalloligands that are introduced before or during the MOF synthesis [69,70]. The incorporation of metallic complexes into the MOF structure can readily be achieved via a direct self-assembly approach (Figure 10.5).…”
Section: Engineering Metal-organic Framework Catalysts By Postsynthementioning
confidence: 99%